THE APPLICATION OF THE TABARAK METHOD IN MEMORIZING THE QUR'AN AND STRENGTHENING THE QURANIC CHARACTER IN THE SAVATY QURANIC SCHOOL; AN EVALUATIVE STUDIES - Laili Tri Lestari; Amir Hamzah; Firdaus; Umar (LP2M IAIM Sinjai, 2025)
This study discusses the evaluation of the tabarak method in memorizing the Qur'an that fosters Qur'anic character, located at the Savaty Qur'an School Makassar. The method used with quantitative evaluative type, so that the data collection method is done with documents, observations, and questionnaires. This study took samples at Sekoloah Qur'an Savaty Makassar by taking a sample of 60 students. The results of this study are as follows: 1) The results of the evaluation of the Tabarak Method planning in memorizing the Quran and cultivating Quranic character are 94% with very good criteria. 2) The evaluation results of the plan to apply the Tabarak Method in memorizing the Quran and cultivating Quranic character are 71% with good criteria. 3) The evaluation results of the Tabarak Method in Memorizing the Quran and Cultivating Quranic Character are 70% with good criteria. These results provide information that the Tabarak Method is a more effective method used in memorizing the Qur'anin in Savaty Qur'an School Makassar and at the same time can grow the character of the Quran.